Research portfolio - Muwanga-Zake, Johnnie Wycliffe Frank (Rhodes University, Faculty of Education, Department of Education, 1999)
A survey carried out during 1998 in rural schools of the South East Region (Butterworth) in the Eastern Cape Province revealed that science teachers do not seem to know their problems in teaching science. Teachers related their problems to lack of apparatus and laboratories. However, it appeared that lack of conceptual understanding of science and of practical skills prevented teachers from preparing practical approaches in the classrooms. Lack of conceptual understanding could have also been the cause of the teacher's inability to innovate and manipulate apparatus. The call for laboratories also seemed to be caused by lack of knowledge of what is done in a laboratory. Practical approaches to science seemed to be further undermined by the irrelevance of apparatus and science in a rural setting, where few community members and teachers might have never used apparatus or done practical exercises anywhere. It is recommended that an integrated approach towards improving science education is required. That is, by means of workshops, all role-players in science education such as teacher training institutions such as Rhodes University, NGOs, the Department of Education and pre-service as well as in-service teachers, should discuss the problems in science education. There is a need to supply basic apparatus and to make sure that in-service and pre-service courses emphasise skills in the use of apparatus, innovating apparatus and practical experiences, along with improving the teacher's conceptual understanding of science. A science college of education is highly recommended to enable a special focus on the plight of science education in the Eastern Cape Province. It also felt that rural areas require special attention in terms of designing outcomes and learning experiences that bear relevance to that environment. The assumption that science education as perceived in industrialised areas can be beneficial everywhere is dangerous and gives science a bad name in rural areas. The survey also showed that triangulation of research instruments is necessary to increase validity and reliability of any research programme. The most useful method appeared to be video recording the interviews.
Keywords: Science -- Study and teaching; Research